2002
DOI: 10.1042/bj3610681
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress inhibits caveolin-1 palmitoylation and trafficking in endothelial cells

Abstract: During normal and pathological conditions, endothelial cells (ECs) are subjected to locally generated reactive oxygen species, produced by themselves or by other vessel wall cells. In excess these molecules cause oxidative injury to the cell but at moderate levels they might modulate intracellular signalling pathways. We have investigated the effect of oxidative stress on the palmitoylation and trafficking of caveolin-1 in bovine aortic ECs. Exogenous H2O2 did not alter the intracellular localization of caveol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Palmitoylation is a reversible modification of proteins that can regulate the localization of proteins in membranes (25,43). Proteins with palmitoylable cysteine residues can cycle between palmitoylated and depalmitoylated states in response to a number of signals, including agonist-induced receptor activation and oxidative stress (11,22,32,33,43). It is not known if flotillin-1 can undergo such cycles of acylation-deacylation under physiological conditions, with associated cycles in its subcellular localization.…”
Section: Discussionmentioning
confidence: 99%
“…Palmitoylation is a reversible modification of proteins that can regulate the localization of proteins in membranes (25,43). Proteins with palmitoylable cysteine residues can cycle between palmitoylated and depalmitoylated states in response to a number of signals, including agonist-induced receptor activation and oxidative stress (11,22,32,33,43). It is not known if flotillin-1 can undergo such cycles of acylation-deacylation under physiological conditions, with associated cycles in its subcellular localization.…”
Section: Discussionmentioning
confidence: 99%
“…None of these fenestrations was observed in the microvasculature of our diabetic rats. In addition, the oxidative stress present in diabetes and known to activate the production of VEGF (Chua et al 1998) was reported to inhibit caveolin palmitoylation and therefore its association with the membrane (Parat et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…One might speculate that oxidative stress alters lipid rafts such that different molecules are recruited to the LPS signaling complex and initiate alternate pathways. In this regard, Parat and colleagues (29) recently demonstrated that oxidative stress was able to inhibit calveolin-1 palmitoylation and trafficking in endothelial cells. Because calveolae may play a role in sequestration of glycosylphosphatidylinositol-linked proteins such as CD14, inhibition of calveolin-1 by oxidant stress may interfere with classical LPS signaling (i.e.…”
Section: Figmentioning
confidence: 99%